Postembolization syndromein the treatment of uterine fibroids (a review) - E. T. Nurmukhametova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The work includes the published results of domestic and foreign studies on the course and correction of post-embolization syndrome that occurs after embolization of the uterine arteries in the treatment of symptomatic uterine fibroids. The articles were searched in the Pubmed, Web of Science, Scopus, Google Scholar, and еLibrary databases.